Chlamydia Positivity in Women Screened in Family Planning Clinics: A Comprehensive Review - Anhar Abdullah Alsadiq et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Chlamydia trachomatis is one of the most prevalent sexually transmitted infections (STIs) globally, with significant implications for women's reproductive health. Screening for Chlamydia in family planning clinics is critical for early detection and prevention of adverse outcomes such as pelvic inflammatory disease, infertility, and ectopic pregnancy. This review explores the prevalence of Chlamydia positivity among women screened in family planning clinics, the associated risk factors, and the role of targeted screening interventions. Current challenges in screening implementation and strategies to improve detection and treatment outcomes are also discussed. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/304 DOI: https://doi.org/10.5281/zenodo.14610813